2014
DOI: 10.1039/c4pp00046c
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of gold–silver alloy nanoparticles for application in metal enhanced bioluminescence

Abstract: In the present study we explored metal enhanced bioluminescence in luciferase enzymes for the first time. For this purpose a simple and reproducible one pot synthesis of gold-silver alloy nanoparticles was developed. By changing the molar ratio of tri-sodium citrate and silver nitrate we could synthesize spherical Au-Ag colloids of sizes ranging from 10 to 50 nm with a wide range of localized surface plasmon resonance (LSPR) peaks (450-550 nm). The optical tunability of the Au-Ag colloids enabled their effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The structural and catalytic changes have been examined for the admixture of gold to silver. 6,7 This property was used in many areas, including antibacterial, 8 bioimaging, 9 bio-labeling, 10 catalysis, 11,12 drug delivery, cancer therapy, 13 nanophotonics, 14 optoelectronics, 15 molecular detection, 16,17 and nanoscale optical biosensors. 18 The physical and chemical properties of nanomaterials are determined by their dimensions and shapes.…”
Section: Introductionmentioning
confidence: 99%
“…The structural and catalytic changes have been examined for the admixture of gold to silver. 6,7 This property was used in many areas, including antibacterial, 8 bioimaging, 9 bio-labeling, 10 catalysis, 11,12 drug delivery, cancer therapy, 13 nanophotonics, 14 optoelectronics, 15 molecular detection, 16,17 and nanoscale optical biosensors. 18 The physical and chemical properties of nanomaterials are determined by their dimensions and shapes.…”
Section: Introductionmentioning
confidence: 99%
“…Active oxygen ions can destroy the reproductive ability of mould in a short time to induce cell death. [4][5][6] Such a mechanism does not need any direct contact between antimicrobial agent and bacteria, because the produced active oxygen ions will automatically diffuse from the bulk metal to the surrounding environment. Nanoparticles exhibit completely new and improved properties based on specic characteristics such as size, distribution and morphology in comparison with their bulk counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists have paid a great deal of attention to nanotechnology, creating a new analysis tool and nanoscale products, which are characterized by significantly different physical and chemical properties, and have a role in the enhancement and improvement of pharmaceutical analysis and other fields . Today, green synthesis and the characterization of gold–silver nanoparticles (Au–AgNPs) have grown exponentially and a number of studies have been reported . Another very important role of Au–AgNP bimetallic alloy is the catalytic effect in which the nanosize particles facilitate chemical processes by enhancing the speed of chemical reactions .…”
Section: Introductionmentioning
confidence: 99%